Exercise induced modulation of immune system functional capacity - Baltopoulos, P. (Biology of Exercise, 2009)
Exercise can have both positive and negative effects on the immune system. Regular moderate exercise seems to reduce the incidence of infection, while prolonged intense exercise causes a temporary suppression of many parameters of immune function, depending on the intensity and duration of exercise. The functional capacity of the immune system is necessary to be determined in order to get useful information about the immune system status of athletes and its impact on performance. In order to investigate the immunological status and depending on the purpose of each study, different laboratory techniques are used. This study aims to review the exercise-induced modulation of immune system functional capacity in terms of cytokines production and WBCs differentiation, as described in the literature.